Improving pitting corrosion resistance of AISI 316L weld overlays via Inconel 82 additions. (2022) - Kaur, Harshdeep; Singh, Harpreet
Abstract: This work was aimed at improving pitting corrosion resistance of AISI 316L weld overlays by adding layers of Inconel 82, a Ni-based superalloy using gas tungsten arc welding (GTAW) process. Weld specimens were subjected to a thermal aging treatment of 750˚C/24 to induce sensitization into the material. Potentiodynamic scan was performed on the weld samples using potentiostat and paracell arrangement, and testing was performed in accordance with ASTM standard G-5. Poteniodynamic anodic polarization (PAP) testing results show that, hybrid composition 316L welds exhibited higher pitting potential and hence better pitting corrosion performance than the conventional 316L welds, both in the as welded as well as sensitized conditions. Aging decreased the pitting resistance of both the welds which was indicated by their lower pitting potential values but the extent of loss of pitting resistance was relatively lesser in hybrid weld overlays. The present work has a significant potential of being recommended to the welding industry, especially the ones dealing into 316L fabrications, as it is established that addition of Inconel 82 layers is found to beneficial in improving the pitting corrosion resistance of 316L weld overlays.